Management of the Frequency Spectrum - William H. Meckling (Washington University Law Quarterly, 1968)
While this Article is directed primarily to discussing alternative systems for managing frequency spectrum, the choice of such a system is not the important barrier to improvement in the existing situation. The real barrier to progress is the problem of provoking political action. Frequency spectrum is managed today in much the same manner as the commons were on feudal estates in the Middle Ages; while we may not be able to prescribe the optimal management system, we can improve substantially on that state of affairs.
Keywords: telecommunications; Spectrum usage; Frequency spectrum